Pengaruh Literasi Keuangan Dan Risiko Terhadap Keputusan Investasi Pada Mahasiswa Program Studi Akuntansi Universitas Pelita Bangsa - Wijaya, Melida; Weni, Desiam Annisa Fitri; Umam, Atiqul; Dasman, Sunita (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
Investment has become a topic of great interest, particulary among university students, as a strategic step in managing finances and buiding future wealth. However investment decision making is influenced by several critical factors, including financial literacy and risk perception, as observed in accounting student at Universitas Pelita Bangsa. This research employs a quantitative method with survey approach. The sampling technique isbased on Slovin’s formula using accidental sampling, involving 89 students from a total population of 420. The primary instrument used is a structured questionnsire measuring financialliteracy, risk perception, and investment decisions. The data were anlyzed using multiple linear regression to examine relationships between variables. The findings of the study indicate that: (1) Financial literacy has a positive and significant effect on students investment decisions. (2) Risk perception also has a positive but not significant effect on investment decisions. (3) Simultaneosly, financial literacy and risk perception have a significant positive impact on students’ investment decisions. This research underscores the importance of financial literacy and risk comprehension in shaping prudent investment decisions, while also advocating for improved financial education among student to address financial challenges in the era of globalization.